Preparation method of porous light composite current collector
By forming a metal nanoactivated layer and plating layer in the composite fluid and punching holes therein, the problems of poor conductivity and complex preparation process of the composite fluid are solved, and the preparation of porous lightweight composite fluid is realized, which improves the battery Cycle performance and safety.
Patent Information
- Application Number
- CN202411337672.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-17
AI Technical Summary
Due to the presence of polymer polymer layer, the composite liquid collector has poor electrical conductivity and complex preparation process, which affects the cycling performance and safety of the battery.
The metal nanoactivated layer is deposited on both sides of the insulating support layer, and then aluminum or copper coating is deposited thereon to form five-layer "sandwich" structures, and multiple through holes that penetrate up and down are formed by laser drilling to obtain a porous lightweight composite set fluid.
It improves the conductivity and mechanical properties of the composite fluid collection, enhances the energy density, power density and safety of the battery, simplifies the preparation process, reduces costs, and is suitable for large-scale production.
Smart Images

Figure CN119324230A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of current collectors, and specifically relates to a method for preparing a porous lightweight composite current collector. Background Art
[0002] As an innovative material, composite current collectors have attracted widespread attention in many fields in recent years. Composite current collectors are a mixture of two or more fluids or materials with different properties. For example, a "sandwich" structure design is adopted, in which the core is composed of a polymer layer, including materials such as PET, PP or PI, and the two sides are covered with metal conductive layers Al or Cu. This structure combines the lightness, flexibility and low cost of polymer materials, making the composite current collector show unique advantages in mechanical strength and corrosion resistance.
[0003] However, due to the presence of the polymer high molecular layer, the conductivity of the composite current collector is poor, and in terms of production technology, the preparation process of some composite current collectors involves the selection of polymer material base film, the deposition and bonding of the metal conductive layer, and subsequent processing and cutting steps, and the operation is relatively complicated. Summary of the invention
[0004] The present application provides a method for preparing a porous lightweight composite current collector, which aims to simplify the operation steps of the composite current collector. The obtained composite current collector is porous and lightweight, has good conductivity, and can improve the cycle performance of electrode materials.
[0005] The present application provides a method for preparing a porous lightweight composite current collector, comprising:
[0006] Depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector;
[0007] Depositing a metal coating of aluminum or copper on both sides of the first composite current collector to obtain a second composite current collector;
[0008] The second composite current collector is laser-drilled to form a plurality of through holes that penetrate from top to bottom, so as to obtain a porous and lightweight composite current collector.
[0009] In a feasible embodiment of the present application, in the step of laser drilling on the second composite current collector to form multiple through holes extending vertically to obtain a porous lightweight composite current collector, the through holes are one of circular through holes and polygonal through holes or a combination thereof.
[0010] In a feasible embodiment of the present application, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the through holes are circular through holes. When the circular through holes are evenly arranged along the first direction, the distance between the circular through holes (hole pitch) is 100 μm to 600 μm, and the diameter (pore size) of the circular through holes is 20 μm to 100 μm.
[0011] In a feasible implementation manner of the present application, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the through holes are circular through holes, and when the circular through holes are evenly arranged along the first direction, the distance between the circular through holes is 1 mm to 4 mm, and the diameter of the circular through holes is 0.5 mm to 5 mm.
[0012] In a feasible embodiment of the present application, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the through holes uniformly arranged along the first direction and the through holes uniformly arranged along the second direction are staggered at an angle of 60°; or; the through holes uniformly arranged along the first direction and the through holes uniformly arranged along the second direction are staggered at an angle of 45°.
[0013] In a feasible implementation manner of the present application, in the step of laser drilling on the second composite current collector to form multiple through holes extending from top to bottom to obtain a porous lightweight composite current collector, the area of the through holes accounts for 40% to 80% of the overall area of the second composite current collector, and can be optionally 53.6% to 74.1%.
[0014] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain a porous lightweight composite current collector, the total thickness of the porous lightweight composite current collector is 3 μm to 10 μm.
[0015] The surface density of the porous lightweight composite current collector is 0.6-2.8 mg / cm 2 , optional 1.0~2.0mg / cm 2 .
[0016] In a feasible implementation manner of the present application, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the laser frequency range is 10kHz to 50kHz, the repetition frequency range is 0.1Hz to 500Hz, the MOPA pulse width is 1ns to 20ns, and the laser speed is 2mm / s to 15mm / s.
[0017] In a feasible embodiment of the present application, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain a porous lightweight composite current collector, the porous lightweight composite current collector at least satisfies one of the following characteristics:
[0018] a. The thickness of the insulating support layer is 2μm to 10μm;
[0019] b. The thickness of the metal nano-activation layer is 5nm to 50nm;
[0020] c. The thickness of the metal coating is 1μm to 5μm.
[0021] In a feasible embodiment of the present application, in the step of depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector, the insulating support layer includes one or more of polyethylene terephthalate, polyvinyl chloride, polyimide, and polypropylene; and / or;
[0022] The metal of the metal nano-activation layer is one or more of Cu, Al, Cr and Ag.
[0023] In a feasible implementation manner of the present application, in the step of depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector, the deposition method includes an atomic deposition method or a magnetron sputtering method.
[0024] In a feasible implementation manner of the present application, in the step of depositing aluminum or copper metal coatings on both sides of the first composite current collector to obtain the second composite current collector, the deposition method includes electroplating, evaporation or chemical plating.
[0025] The present application uses a polymer insulating support layer as a "sandwich" layer, deposits metal nano-activation layers on its upper and lower surfaces respectively, and then deposits metal aluminum or metal copper plating layers on the upper and lower layers of the current collector forming the metal nano-activation layer to form a five-layer "sandwich" structure, wherein the polymer insulating support layer can shrink due to heat when the battery is short-circuited to form a local collapse of the current collector, thereby cutting off the short-circuit loop; the metal nano-activation layer can enhance the compatibility and adhesion of the outermost conductive layer and the support layer to improve the mechanical and electrical properties of the composite current collector.
[0026] The present application further punches holes on the five-layer "sandwich" structure composite current collector to form a number of through holes that pass through from top to bottom. First, the mass of the current collector is reduced and the surface area of the current collector is increased, which can improve the energy density and power density of the battery; second, the through holes help to dissipate the heat released by the battery during the charging and discharging process, reduce thermal runaway caused by heat accumulation, and improve the safety and cycle life of the battery; third, the through holes can connect the slurry on both sides of the current collector, improve the integrity and adhesion of the slurry, reduce the phenomenon of slurry shedding, and can also reduce the contact resistance between the current collector and the active material, reduce the internal resistance of the battery cell, and improve the conductivity of the battery; fourth, the through holes can induce dendrites to grow into the void, accommodate lithium precipitated during the charging and discharging process, avoid excessive growth of lithium dendrites to damage the conductive layer, and improve the safety of lithium metal batteries; fifth, after laser etching, the through holes help to improve the bonding strength of the insulating support polymer layer and the metal layer; sixth, the composite current collector structure of the present application is relatively simple, which can save costs, the material has good compatibility, and is porous and lightweight, which is conducive to large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is a schematic diagram of the second composite current collector shown in Example 1;
[0028] Among them, 1, PET poly-edge support layer; 2-1, metal copper nano-activation layer; 2-2, metal copper nano-activation layer; 3-1, copper metal plating layer; 3-2, copper metal plating layer;
[0029] Figure 2 It is a schematic diagram of the 60° staggered arrangement of circular through holes;
[0030] Figure 3 It is a schematic diagram of circular through holes staggered at 45°;
[0031] Figure 4 is the SEM image of the current collector sample;
[0032] Figure 5 It is the SEM image of the current collector sample. DETAILED DESCRIPTION
[0033] In order to make the invention purpose, technical scheme and beneficial technical effect of the present application clearer, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the embodiments described in this specification are only for explaining the present application, not for limiting the present application.
[0034] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.
[0035] In the description herein, when a composition is described as containing, comprising or including specific components, or when a process is described as containing, comprising or including specific process steps, it is expected that the composition of the present application also consists essentially of or consists of the components, and the process of the present application also consists essentially of or consists of the process steps.
[0036] The use of the terms "including," "comprising," "containing," and "having" should generally be interpreted as open ended and non-limiting unless expressly stated otherwise.
[0037] In the description of this article, it should be noted that, unless otherwise specified, “above” and “below” are inclusive of the number itself, and the “multiple” in “one or more” means more than two.
[0038] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.
[0039] In the application of battery pole pieces, the mechanical properties of the composite current collector are also excellent, especially in terms of tensile resistance and puncture resistance, which helps to extend the service life of the battery.
[0040] However, due to the presence of polymer materials in the composite current collector, the polymer materials have poor compatibility with the conductive layer, poor bonding strength, poor conductivity, and are prone to separation after multiple charge and discharge cycles, affecting the electrochemical properties of the battery, especially the safety performance and cycle performance. In addition, some composite current collectors have a large variety of materials, high cost, and large weight, which not only affects the energy density of the battery, but is also not conducive to large-scale production.
[0041] In view of this, the inventors provide a method for preparing a porous lightweight composite current collector in the present application. The obtained composite current collector is porous and lightweight, has good electrical conductivity, and can improve the cycle performance of electrode materials.
[0042] In an embodiment of the present application, a method for preparing a porous lightweight composite current collector is provided, comprising:
[0043] Depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector;
[0044] Depositing a metal coating of aluminum or copper on both sides of the first composite current collector to obtain a second composite current collector;
[0045] The second composite current collector is laser-drilled to form a plurality of through holes that penetrate from top to bottom, so as to obtain a porous and lightweight composite current collector.
[0046] The present application uses a polymer insulating support layer as a "sandwich" layer, deposits metal nano-activation layers on its upper and lower surfaces respectively, and then deposits metal aluminum or metal copper plating layers on the upper and lower layers of the current collector forming the metal nano-activation layer to form a five-layer "sandwich" structure, wherein the polymer insulating support layer can shrink due to heat when the battery is short-circuited to form a local collapse of the current collector, thereby cutting off the short-circuit loop; the metal nano-activation layer can enhance the compatibility and adhesion of the outermost conductive layer and the support layer to improve the mechanical and electrical properties of the composite current collector.
[0047] The present application further punches holes on the five-layer "sandwich" structure composite current collector to form a number of through holes that pass through from top to bottom. First, the mass of the current collector is reduced and the surface area of the current collector is increased, which can improve the energy density and power density of the battery; second, the through holes help to dissipate the heat released by the battery during the charging and discharging process, reduce thermal runaway caused by heat accumulation, and improve the safety and cycle life of the battery; third, the through holes can connect the slurry on both sides of the current collector, improve the integrity and adhesion of the slurry, reduce the phenomenon of slurry shedding, and can also reduce the contact resistance between the current collector and the active material, reduce the internal resistance of the battery cell, and improve the conductivity of the battery; fourth, the through holes can induce dendrites to grow into the void, accommodate lithium precipitated during the charging and discharging process, avoid excessive growth of lithium dendrites to damage the conductive layer, and improve the safety of lithium metal batteries; fifth, after laser etching, the through holes help to improve the bonding strength of the insulating support polymer layer and the metal layer; sixth, the composite current collector structure of the present application is relatively simple, which can save costs, the material has good compatibility, and is porous and lightweight, which is conducive to large-scale production.
[0048] The shape of the through hole can be circular, triangular, square, rectangular, rhombus or other shapes. In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes that penetrate up and down to obtain a porous lightweight composite current collector, the through hole is one of a circular through hole and a polygonal through hole or a combination thereof.
[0049] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the through holes are circular through holes. When the circular through holes are evenly arranged along the first direction, the distance between the circular through holes (hole pitch) is 100 μm to 600 μm, and the diameter (pore size) of the circular through holes is 20 μm to 100 μm.
[0050] Without intending to be limited by any theory or explanation, the inventors have found that, for example, when the through holes on the lightweight composite current collector used in conventional lithium-ion batteries are within the above-mentioned pore size and pore spacing ranges, the lightweight composite current collector can ensure no leakage and smooth coating during the coating process, and the electrode sheet obtained by coating has the characteristics of a smooth surface, no wrinkles, and no obvious burrs.
[0051] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain a porous lightweight composite current collector, the through holes are circular through holes, and when the circular through holes are evenly arranged along the first direction, the distance between the circular through holes is 1 mm to 4 mm, and the diameter of the circular through holes is 0.5 mm to 5 mm.
[0052] Without intending to be bound by any theory or explanation, the inventors have found that, for example, the current collector used in the negative electrode of a lithium metal battery with a higher energy density, the above-mentioned pore size and pore spacing are more conducive to the adhesion with a lithium strip or a microporous lithium membrane.
[0053] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain a porous lightweight composite current collector, when the through holes are uniformly arranged along the first direction, they are staggered at an angle of 60° with the through holes uniformly arranged along the second direction; or; when the through holes are uniformly arranged along the first direction, they are staggered at an angle of 45° with the through holes uniformly arranged along the second direction.
[0054] It is not intended to be limited by any theory or explanation. The above two opening methods have high strength and wide porosity in the form of triangles, which is beneficial to fully connect the slurry on both sides of the current collector. On the basis of improving the conductivity, it is beneficial to improve the mechanical stability of the porous lightweight composite current collector, which is not easy to deform or rupture, thereby improving the safety performance and cycle performance of the battery.
[0055] In a feasible implementation manner of the present application, in the step of laser drilling on the second composite current collector to form multiple through holes extending from top to bottom to obtain a porous lightweight composite current collector, the area of the through holes accounts for 40% to 80% of the overall area of the second composite current collector, and can be optionally 53.6% to 74.1%.
[0056] Without intending to be limited by any theory or explanation, when the area ratio of the through holes of the porous lightweight composite current collector of the present application is within the above range, the energy density and cycle performance of the battery can be taken into account. If the ratio is too high, the amount of electrode active material that can be attached will be reduced, reducing the energy density, and may increase the risk of electrolyte leakage, pollute the environment, and reduce safety performance. If the ratio is too low, the conductivity will not be significantly improved.
[0057] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain a porous lightweight composite current collector, the total thickness of the porous lightweight composite current collector is 3 μm to 10 μm.
[0058] The surface density of the porous lightweight composite current collector is 0.6-2.8 mg / cm 2 , optional 1.0~2.0mg / cm 2 .
[0059] Without intending to be limited by any theory or explanation, the composite current collector of the present application has a relatively small thickness and surface density, which can reduce the mass of inactive materials in the battery cells, so that the battery can accommodate more active materials at the same weight, thereby improving the energy density of the battery.
[0060] In some embodiments, in the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain a porous lightweight composite current collector, the laser frequency range is 10kHz to 50kHz, the repetition frequency range is 0.1Hz to 500Hz, the MOPA pulse width is 1ns to 20ns, and the laser speed is 2mm / s to 15mm / s.
[0061] In some embodiments, the porous lightweight composite current collector satisfies at least one of the following characteristics:
[0062] a. The thickness of the insulating support layer is 2μm to 10μm;
[0063] b. The thickness of the metal nano-activation layer is 5nm to 50nm;
[0064] c. The thickness of the metal coating is 1μm to 5μm.
[0065] Without intending to be limited by any theory or explanation, when the thickness of the insulating support layer is controlled within the above range, the conductivity, mechanical strength and safety performance of the current collector can be balanced. If it is too thick, the conductivity of the current collector will be reduced and the internal resistance will be increased. If it is too thin, the safety performance and mechanical strength will be reduced. When the thickness of the metal nano activation layer is controlled within the above range, the insulating support layer can be activated well, the outer conductive layer and the insulating support layer can be bonded together, and the uniformity and density of the outermost conductive layer on the insulating support layer can be improved, and the conductivity of the current collector can be improved; if it is too thick, the cost will increase, and if it is too thin, the activation effect will be poor, and it will be difficult to bond the outer conductive layer and the insulating support layer well, affecting the stability and conductivity of the current collector.
[0066] In some embodiments, in the step of depositing a metal nano-active layer on both sides of the insulating support layer to obtain a first composite current collector, the insulating support layer includes one or more of polyethylene terephthalate, polyvinyl chloride, polyimide, and polypropylene; and / or;
[0067] The metal of the metal nano-activation layer is one or more of Cu, Al, Cr and Ag.
[0068] In some embodiments, in the step of depositing a metal nano-active layer on both sides of the insulating support layer to obtain the first composite current collector, the deposition method includes an atomic deposition method or a magnetron sputtering method.
[0069] The atomic deposition method or magnetron sputtering method can make the metal nano-activated layer deposited more uniformly and densely, which is beneficial to activate the insulating support layer and enable the insulating support layer and the outer metal coating to be better bonded together.
[0070] In some embodiments, in the step of depositing aluminum or copper metal coatings on both sides of the first composite current collector to obtain the second composite current collector, the deposition method includes electroplating, evaporation or chemical plating.
[0071] Example
[0072] The following examples more specifically describe the disclosure of the present application, which are intended for illustrative purposes only, as it will be apparent to those skilled in the art that various modifications and variations are possible within the scope of the disclosure of the present application. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0073] Example 1
[0074] A method for preparing a porous lightweight composite current collector, comprising:
[0075] PET is selected as the polymer layer, and a 20nm metal copper activation layer is firstly sputtered on both sides of the polymer by magnetron sputtering to obtain a first composite current collector; 5μm of metal copper is electroplated on both sides of the first composite current collector by water electroplating to obtain a second composite current collector, such as Figure 1 As shown;
[0076] The following laser drilling parameters were set: laser frequency 10 kHz, repetition frequency range 100 Hz, MOPA pulse width 5 ns, speed 7 mm / s, and laser drilling was performed on the second composite current collector.
[0077] Draw a laser punching template file, the punching pattern is: 60° staggered circular holes, 1mm hole diameter, 1.5mm hole spacing. According to the drawn punching template file and the set laser parameters, continuously punch holes to form multiple through holes that penetrate from top to bottom to obtain a porous lightweight composite current collector.
[0078] Example 2
[0079] The difference from Example 1 is that polyimide PI is selected as the polymer layer, and other conditions remain unchanged.
[0080] Example 3
[0081] The difference from Example 1 is that the metal copper coating is prepared by evaporation, the coating thickness is 1.5 μm, and other conditions remain unchanged.
[0082] Example 4
[0083] The difference from Example 1 is that the thickness of the metal nano activation layer is 2 nm, and other conditions remain unchanged.
[0084] Example 5
[0085] The difference from Example 1 is that the laser drilling parameter settings are different. The parameters set in this example are laser frequency 50 kHz, repetition frequency range 400 Hz, MOPA pulse width 20 ns, speed 15 mm / s, and other conditions remain unchanged.
[0086] Example 6
[0087] The difference from Example 1 is that the punching pattern is: circular holes staggered at 60°, the hole diameter is 50 μm, the hole spacing is 200 μm, and other conditions remain unchanged.
[0088] Example 7
[0089] The difference from Example 1 is that the punching pattern is: circular holes staggered at 45°, the hole diameter is 100 μm, the hole spacing is 150 μm, and other conditions remain unchanged.
[0090] Example 8
[0091] The difference from Example 1 is that the punching pattern is: circular holes staggered at 45°, the hole diameter is 10 μm, the hole spacing is 50 μm, and other conditions remain unchanged.
[0092] Example 9
[0093] The difference from Example 1 is that the punching pattern is: circular holes staggered at 45 degrees, the hole diameter is 2 mm, the hole spacing is 5 mm, and other conditions remain unchanged.
[0094] Example 10
[0095] The difference from Example 1 is that the punching pattern is a straight row of round holes, and the rest remains unchanged.
[0096] Embodiment 11
[0097] The difference from Example 1 is that the punching pattern is a straight row of oblong holes with a length of 2 mm and a width of 5 mm, and the rest remains unchanged.
[0098] Comparative Example 1
[0099] The difference from Example 1 is that no holes are punched after the second composite current collector is obtained.
[0100] Comparative Example 2
[0101] The difference from Example 1 is that the activation layer is not prepared by magnetron sputtering, but the metal copper is directly electroplated on the surface of PET. Other conditions remain unchanged.
[0102] Each current collector was tested, and the results are shown in Table 1 below.
[0103] Table 1:
[0104]
[0105] The above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a porous lightweight composite current collector, characterized in that: The preparation method comprises: Depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector; Depositing a metal coating of aluminum or copper on both sides of the first composite current collector to obtain a second composite current collector; The second composite current collector is laser-drilled to form a plurality of through holes that penetrate from top to bottom, so as to obtain the porous lightweight composite current collector.
2. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain the porous lightweight composite current collector, the through holes are circular through holes. When the circular through holes are evenly arranged along the first direction, the distance between the circular through holes is 100 μm to 600 μm, and the diameter of the circular through holes is 20 μm to 100 μm.
3. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain the porous lightweight composite current collector, the through holes are circular through holes. When the circular through holes are evenly arranged along the first direction, the distance between the circular through holes is 1 mm to 4 mm, and the diameter of the circular through holes is 0.5 mm to 5 mm.
4. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling holes on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain the porous lightweight composite current collector, the through holes uniformly arranged along the first direction and the through holes uniformly arranged along the second direction are staggered at an angle of 60°; or; The through holes uniformly arranged along the first direction and the through holes uniformly arranged along the second direction are staggered at an angle of 45°.
5. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling holes on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain the porous lightweight composite current collector, the area of the through holes accounts for 40% to 80% of the overall area of the second composite current collector.
6. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling on the second composite current collector to form a plurality of through holes extending from top to bottom to obtain the porous lightweight composite current collector, the laser frequency range of the laser drilling is 10kHz to 50kHz, the repetition frequency range is 0.1Hz to 500Hz, the MOPA pulse width is 1ns to 20ns, and the laser speed is 2mm / s to 15mm / s.
7. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: The porous lightweight composite current collector meets at least one of the following characteristics: a. The thickness of the insulating support layer is 2μm to 10μm; b. The thickness of the metal nano-activation layer is 5nm to 50nm; c. The thickness of the metal coating is 1 μm to 5 μm.
8. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector, the insulating support layer comprises one or more of polyethylene terephthalate, polyvinyl chloride, polyimide, and polypropylene; and / or; The metal of the metal nano activation layer is one or more of Cu, Al, Cr and Ag.
9. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of depositing a metal nano-activation layer on both sides of the insulating support layer to obtain a first composite current collector, the deposition method includes an atomic deposition method or a magnetron sputtering method; and / or; In the step of depositing aluminum or copper metal coatings on both sides of the first composite current collector to obtain the second composite current collector, the deposition method includes electroplating, evaporation or chemical plating.
10. The method for preparing a porous lightweight composite current collector according to claim 1, characterized in that: In the step of laser drilling on the second composite current collector to form a plurality of through holes extending vertically therethrough to obtain the porous lightweight composite current collector, the through holes are circular through holes and polygonal through holes or a combination thereof.
Citation Information
Patent Citations
Composite current collector, preparation method thereof and lithium battery pole piece
CN111883777A
Preparation method of negative electrode composite current collector and product prepared by preparation method
CN114678534A
Composite current collector and preparation method and application thereof
CN115207366A
Composite current collector, preparation method thereof and battery comprising composite current collector
CN116706086A
Composite current collector, electrode plate and preparation method
CN118553918A